Anti-Cancer Drugs - Nature, Synthesis and Cell 2016
DOI: 10.5772/66175
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products for Treatment of Chronic Myeloid Leukemia

Abstract: Chronic myeloid leukemia (CML) is a hematological malignancy that arises due to reciprocal translocation of 3′ sequences from c-Abelson (abl) protooncogene on chromosome 9 with 5′ sequence of truncated break point cluster region (bcr) to chromosome 22. The fusion gene product BCR-ABL, a functional oncoprotein p210, is a constitutively activated tyrosine kinase that activates several cell proliferative signaling pathways. BCR-ABL-specific tyrosine kinase inhibitors (TKIs) such as imatinib, nilotinib and ponatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 240 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Chronic myeloid leukemia cells may also acquire resistance to imatinib by different mechanisms, such as P-gp overexpression ( 35 , 36 ). Some researchers have obtained different results with different flavonoids ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic myeloid leukemia cells may also acquire resistance to imatinib by different mechanisms, such as P-gp overexpression ( 35 , 36 ). Some researchers have obtained different results with different flavonoids ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several secondary metabolites from natural origin such as alkaloids, flavonoids, terpenoids, polyketides, lignans, saponins, and peptides exhibited a potent anti-CML activity (Khajapeer and Baskaran 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is evidenced from an earlier study that many natural products such as polyphenolic acids, flavonoids, alkaloids, terpenoids, polyketides, saponins and lignans have capacity to inhibit cell proliferation during the development of CML through the induction of apoptosis. [3] A natural phenolic compound, Hydroxychavicol (HCH) is found in Piper betle leaves with potential anti-mutagenic properties. [4] Previous studies have shown its protective efficacy against multiple cancer cells including oral cancer, [5] prostate cancer and chronic myeloid lymphoma.…”
Section: Abstract a R T I C L E I N F Omentioning
confidence: 99%
“…It was estimated approximately 90% of CML patients have shortened chromosome called "Philadelphia chromosome". [2,3]…”
Section: Introductionmentioning
confidence: 99%